The end of her : a novel - Lapeña, Shari, 1960- (Pamela Dorman Books/Viking, 2020)
"The new domestic suspense novel from the New York Times bestselling author of The Couple Next Door and Someone We Know. In upstate New York, Stephanie and Patrick are adjusting to life with their colicky twin babies. The girls are a handful, but Stephanie doesn't mind being a stay-at-home mom, taking care of them while Patrick does the nine to five to pay the bills. When a woman from Patrick's past drops in on them unexpectedly, raising questions about his late first wife, Stephanie supports her husband wholeheartedly. She knows the car accident all those many years ago was just that--an accident. But Erica is persistent, and now she's threatening to go to the police. Patrick is afraid his job--and his reputation--will be at risk if he doesn't put an end to Erica's questioning immediately. And when the police start digging, Stephanie's trust in her husband begins to falter and Patrick is primed to lose everything he loves. As their marriage crumbles, Stephanie feels herself coming unglued, and soon she isn't sure what--or who--to believe. Now the most important thing is to protect her girls, but at what cost?"--